ホウ素吸着剤のリサイクル方法 (2017)
PROBLEM TO BE SOLVED: To effectively recycle a boron adsorbent deteriorated in a polymer resin.SOLUTION: A deteriorated boron adsorbent is mixed with an organic solvent so as to be a slurry in which a polymer resin in the boron adsorbent is dissolved, and this slurry is granulated. By controlling the viscosity expressed in terms of 50°C of the slurry to be fed to the granulation into 200 to 1,600 cP, it can be granulated into a satisfactory shape and can be recycled. Preferably, the deteriorated boron adsorbent is subjected to acid pickling and alkali cleaning, is thereafter dried, and is subsequently dissolved into the organic solvent.